Implementation of Augmented Reality (AR) in the Development of Space Building Modeling Learning Media for Elementary School Students 040481 Juma Raja Village - Manurung, Asrar Aspia; Sari, Indah Purnama; Manurung, Sri Hariani (Indonesian Journal of Education and Mathematical Science, 2024)
A geometric shape or also called a geometric shape is a three-dimensional shape that has space and is limited by sides. Spatial structure is a characteristic of concrete objects that we often encounter every day. Rapid technological advances in the world of information technology and computers also have an impact on the world of education, which offers various conveniences and innovations. Augmented Reality or often abbreviated as AR is a technology that is able to combine real and virtual situations at one time which is displayed in real time. With AR technology, it is hoped that it can provide innovation and new learning experiences in recognizing and studying spatial shapes, so that it can attract the interest of students who are studying it.